(untitled) (Scientific journal of the Fergana State University, 2023)
The use of information technology in education and pedagogical activities, the teaching of modern electrical equipment increases the effectiveness of lessons, the use of telecommunications, visualization and STEAM methods develops students’ imagination, can find several solutions to problem situations, high level of knowledge effectively helps them to become qualified professionals in the future. There are several methods aimed at bringing the level of education of teachers in Uzbekistan to the level of education in developed countries.